2018
DOI: 10.1016/j.renene.2017.10.079
|View full text |Cite
|
Sign up to set email alerts
|

Biobutanol production using pea pod waste as substrate: Impact of drying on saccharification and fermentation

Abstract: PDF/A is an ISO-standardized version of the Portable Document Format (PDF) specialized for the digital preservation of electronic documents. The extension in the file name is pdf. PDF/A differs from "normal" PDF in that features ill-suited for long-term archiving are omitted. PDF/A embeds all fonts used in the document within the PDF file, so that the user of your file will not have to have the same fonts that you used to create the file installed on their computer in order to read it. Recommended versions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 47 publications
2
22
0
1
Order By: Relevance
“…Similar values of total ABE (4–6 g L −1 ) were obtained by Nimbalkar et al. [ 51 ] using C. acetobutylicum to ferment pea residues with a similar procedure.…”
Section: Processing Of Fvwsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar values of total ABE (4–6 g L −1 ) were obtained by Nimbalkar et al. [ 51 ] using C. acetobutylicum to ferment pea residues with a similar procedure.…”
Section: Processing Of Fvwsupporting
confidence: 83%
“…[ 113 ] Nimbalkar et al. [ 51 ] have pointed out that the high holocellulose content of pea pod waste means that these residues can be used as a potential raw material for butanol production.…”
Section: Fvw As Substrates To Obtain Different Productsmentioning
confidence: 99%
“…3 In general, more than 30% (w/w) waste is produced during pea harvesting, which is often left on farmland. 4 Anecdotally, more than enough pea waste is left on land maintaining soil health and nutrition. Thus, there is an excess which serves no additional benefit and probably decays.…”
Section: Introductionmentioning
confidence: 99%
“…Research done by Olivia-Rodriguez et al [33], demonstrated that agave hydrolysate has the potential for ABE production using co-culture of Bacillus subtilis CDBB 555 and Clostridium acetobutylicum ATCC 824 without anaerobic pretreatment. Nimbalkar et al [34], investigated the production of ABE by using pea pod waste as feed material. The investigation leads to a result where the ABE fermentation of detoxified pea pod waste reveals a low production of total solvent with approximately 50% utilization of sugars.…”
Section: Feedstock Selectionsmentioning
confidence: 99%